A Comparison of Using Oral Misoprostol and Manual Vacuum Aspiration (MVA) in the First Trimester Incomplete Abortion - Chowdhury, Farhana Hyder; Sehar, Nazmun; Huda, Reaz Mahmud; Alam, Mohammad Ashraful; Hossain, Md Delwar; Akbar, Mohammad Shafiqullah (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Misoprostol, a synthetic prostaglandin E1 analogue, may workas an alternative to manual vacuum aspiration (MVA) in incomplete abortion, which is easy to administer orally, andhelps to increase access to post abortion care. Objective: To compare the effectiveness, safety and acceptability by the patients of using oral misoprostol therapy and manual vacuum aspiration technique for the treatment of incomplete abortion in the first trimester of pregnancy. Methods: This cross-sectional study was conducted in Department of Obstetrics & Gynaecology, Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh, between January and July of 2016. A total of 200 patients (women with incomplete abortion ≤12weeks) were enrolled in the study. 100 Patients were randomly selected and treated with oral misoprostol 600mcg (group I), while the other 100 were treated with manual vacuum aspiration (MVA) (group II). They were followed up for 1-3 days before discharge. Participants were asked to return to the clinic for follow-up after 1 week. In follow-up visit, if abortion was not found complete, an immediate surgical evacuation was performed. Results: The mean age of the participants were 28.59±10.44 and 28.24±9.40 in group I and II respectively. In group I, 94% had complete abortion, while 6% had incomplete abortion or continued pregnancy. However, in group II, 100% had complete abortion (P>0.05). Per vaginal normal and heavy bleeding were 35% and 12% in group I, while 9% and 1% in group II respectively (P<0.001). Pain, nausea, vomiting and gastrointestinal issues were more observed in group I than that of group II (P<0.001). However, incidence of fever, headache and vertigo were similar in both groups (P<0.001). In group I, 98% stated that the treatment was ‘satisfactory/very satisfactory’, while in group II, 99% found the procedure ‘satisfactory/very satisfactory’. The difference between the groups is not statistically significant (P>0.05). In group I, 98% stated that they would select this method again, if needed and recommend it to a friend or relative, while in group II, 88% stated that they would choose this method again and 86% would like to recommend to a friend or relative. The difference between the groups is statistically significant (P<0.001). Conclusion: Our data suggest that oral misoprostol therapy can be used effectively ensuring safety and patients’ satisfaction for treatment of incomplete abortion in the first trimester as compared to manual vacuum aspiration technique. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 173-177